Analisis Kesiapan Pemerintah Daerah Kota Payakumbuh Menerapkan 30% Belanja Pegawai Pada Tahun 2027 - Andriani, Riza (Polytechnic of State Finance STAN, 2025)
The enactment of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (HKPD Law) forced regional governments to limit regional employee spending excluding teacher allowances allocated through Transfers to Regions (TKD) to a maximum of 30% of budget expenditures. The HKPD Law was required to be implemented no later than 2027 to ensure maximum employee spending obligations were met. This situation was faced by the Payakumbuh City Government, where the proportion of employee spending before the enactment of the HKPD Law, in 2021, was still at 46%. This situation did not change after the enactment of the HKPD Law in 2025. The portion of employee spending to total APBD expenditure in 2025 was 52%, an increase of 6%. An interesting research question was what factors triggered the increase in the portion of employee spending to Payakumbuh City APBD expenditure, and what efforts needed to be made. The study results indicated that the portion of employee spending to total APBD expenditure was projected to be insufficient to meet the maximum percentage of employee spending to total expenditure. Research data showed that of the 52% of employee spending in 2025, after deducting additional teacher income and teacher allowances, it was 46%. This figure was still far from the target of 30% of employee spending. Therefore, efforts were needed to reduce the portion of employee spending to total regional expenditure,In addition, the central government needed to evaluate policies.